Analisis Sedimentasi Saluran Drainase Perkotaan Berdasarkan Pengukuran Lapangan Di Jalan Taduan–Jalan Taut Kota Medan - Jesrelita Romauli Silalahi; Intan Permata Sari Silaban; Yuni Yolanda (Jurnal Teknologi Lingkungan, 2026)
This study aims to analyze the level of sedimentation in urban drainage channels and evaluate its effect on channel capacity along Taduan–Taut Streets, Medan City. The research was conducted through direct field measurements at 10 drainage channel segments to obtain data on channel dimensions, sediment thickness, and sediment characteristics, supported by secondary data on rainfall and population growth. The results indicate that sediment thickness ranges from 0.01 m to 0.36 m, with sediment volumes varying between 2.046 m³ and 133.92 m³. The highest sediment accumulation was found in Segment II and Segment X, resulting in a reduction of the effective drainage channel capacity. High annual rainfall and increasing population growth further contribute to sediment accumulation and drainage burden. The novelty of this study lies in the integration of direct field-based sedimentation measurements with rainfall and population growth analyses to evaluate their combined influence on urban drainage performance. The findings demonstrate that sedimentation significantly reduces drainage efficiency and highlight the importance of routine maintenance and sustainable sediment management to improve urban drainage system performance